Preliminary Screening of Pyrene-Degrading Bacteria from the Semi-Anoxic Bovine Gut (Sahel Journal of Life Sciences FUDMA, 2026)
Polycyclic aromatic hydrocarbons (PAHs) are environmental contaminants whose remediation remains a global challenge in oxygen-limited and resource-constrained environments. While microbial degradation of PAHs has been studied in soils and aquatic systems, the gastrointestinal microbiota of ruminants remains largely unexplored as a potential reservoir of hydrocarbon-degrading bacteria. This study evaluates the PAH-degrading potential of bacterial isolates from the semi-anoxic intestinal lining of cows inhabiting crude oil-impacted environments. Samples were aseptically collected from the intestinal gut lining of Bos tarus at the point of slaughter and cultured with a Pyrene-supplemented Bushnell Haas medium. A total of sixteen distinct bacterial isolates were obtained and characterized using morphological and biochemical techniques. Their capacity to metabolize pyrene, a model high-molecular-weight PAH, was assessed using a 2,6-dichlorophenol indophenol (DCPIP) redox assay in combination with growth kinetics monitoring (OD₆₀₀nm). Approximately 70% of the isolates demonstrated DCPIP reduction, indicating active redox metabolism associated with hydrocarbon utilization. Notably, Citrobacter freundii and Pseudomonas alcaligenes exhibited pronounced and sustained DCPIP reduction alongside measurable shifts in growth dynamics, suggesting enhanced metabolic adaptation to pyrene. The applied methods provide preliminary evidence of PAH-associated metabolic activity; the observed diversity among isolates highlights the functional versatility of gut-associated microbiota under semi-anoxic conditions. These findings position the ruminant intestinal microbiome as an underutilized source of bacteria with potential relevance for bioremediation in oxygen-limited environments and present a low-cost screening framework suitable for resource-limited laboratories and provide a foundation for further investigations involving molecular identification, enzymatic pathway analysis, and analytical validation of hydrocarbon degradation.